A high temperature resistant ternary aerogel composite material and preparation method thereof

By preparing silicon-aluminum sol and composite silicon nitride whiskers, combined with pretreatment and multiple impregnation steps, a high-performance ternary aerogel composite material is formed, which solves the problem of insufficient performance of existing materials at high temperatures and achieves excellent thermal insulation, strength and thermal shock resistance.

CN119161200BActive Publication Date: 2025-03-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411613063.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The application of existing ternary aerogel composites in hypersonic aircraft is limited, mainly due to their insufficient thermal insulation, strength, toughness and thermal shock resistance at high temperatures, and poor hydrophobicity.

Method used

By preparing silicon-aluminum sol and composite silicon nitride whiskers, combined with pretreatment and multiple impregnation steps, a composite material consisting of silicon nitride fiber fabric, silicon dioxide aerogel and aluminum trioxide aerogel is formed to improve its high temperature performance and hydrophobicity.

Benefits of technology

It has achieved excellent thermal insulation, strength, toughness, high-temperature oxidation resistance, thermal shock resistance and hydrophobicity of high-temperature resistant tri-aerogel composite materials, and has a small density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-temperature resistant ternary aerogel composite material and a preparation method thereof, belonging to the technical field of thermal insulation materials. The preparation method comprises the following steps: preparing a silicon-aluminum sol, preparing a composite silicon nitride whisker, pretreatment, primary impregnation, and secondary impregnation; the preparation of the composite silicon nitride whisker comprises the following steps: surface modification, primary compounding, and secondary compounding; the pretreatment comprises mixing methyltrimethoxysilane and anhydrous ethanol, stirring at room temperature, adding silicon nitride fiber fabric, stirring at 60-65 DEG C, filtering, cleaning the filter residue and vacuum drying, mixing with polyvinyl pyrrolidone and water, stirring at room temperature, filtering, cleaning the filter residue and vacuum drying to obtain the pretreated silicon nitride fiber fabric; the high-temperature resistant ternary aerogel composite material prepared by the invention has excellent thermal insulation, strength, toughness, high-temperature oxidation resistance, thermal shock resistance, hydrophobicity, and also has a relatively low density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat insulation materials, and in particular to a high temperature resistant ternary aerogel composite material and a preparation method thereof. Background Art

[0002] Hypersonic aircraft refer to winged or wingless aircraft such as aircraft, missiles, and artillery shells that fly at speeds exceeding five times the speed of sound. They have the characteristics of a high success rate of penetration and have enormous military value and potential economic value.

[0003] One of the problems encountered in the development of hypersonic aircraft is the aerodynamic heating problem. When a hypersonic aircraft is flying, due to the effects of shock waves and viscosity, the air temperature around the hypersonic aircraft rises sharply, forming a severe aerodynamic heating environment. Therefore, in order to ensure the safety performance of hypersonic aircraft, it is necessary to perform thermal protection on the surface of the hypersonic aircraft. For thermal protection materials, in order to ensure the flight performance of hypersonic aircraft, they need to have excellent thermal insulation, strength, toughness, high temperature oxidation resistance, thermal shock resistance, hydrophobicity, and a relatively low density.

[0004] Aerogel is a nanoporous material composed of gas and solid, with extremely high porosity and specific surface area, which makes aerogel show excellent performance in the fields of thermal insulation, heat preservation, adsorption, etc. The excellent thermal insulation performance of aerogel makes it an ideal material for thermal protection of hypersonic aircraft.

[0005] Silica aerogel has extremely low thermal conductivity, which is less than 0.02W / (m·K) at room temperature and less than 0.05W / (m·K) at 800°C. It also has a low density and is widely used in the aerospace field. However, since the long-term operating temperature of silica aerogel is 650-800°C, it is difficult to meet the requirements for use at higher temperatures, which limits the application of silica aerogel in hypersonic aircraft.

[0006] Alumina aerogel also has the advantage of low density, and compared with silica aerogel, it has better high temperature resistance and can withstand high temperatures below 1000°C. However, above 1000°C, alumina aerogel will undergo a series of phase changes, causing the alumina aerogel to shrink and increase the thermal conductivity.

[0007] Experiments have found that the composite aerogel prepared by combining silica aerogel with alumina aerogel has a skeleton composed of pearl chains and lamellar structures stacked on top of each other, which can withstand high temperatures above 1000°C. However, the strength and toughness of the composite aerogel are poor.

[0008] Considering that silicon nitride has the advantages of high hardness, high strength, good resistance to high temperature oxidation, and good thermal shock resistance, the inventors have tried to compound silicon nitride fibers into composite aerogels prepared from silica aerogel and alumina aerogel to obtain an aerogel composite material with excellent comprehensive performance. During the compounding, the silicon nitride fiber fabric is completely immersed in the silica-alumina sol, and then gelled and treated at high temperature to obtain a ternary aerogel composite material. However, the ternary aerogel composite material prepared by the above method has the following two shortcomings: First, due to the poor hydrophobicity of silica aerogel and alumina aerogel, the hydrophobicity of the obtained ternary aerogel composite material is poor; second, due to the poor bonding force between silicon nitride fibers and silica aerogel and alumina aerogel, the silica aerogel and alumina aerogel are unevenly distributed in the silicon nitride fiber fabric, which further leads to poor thermal insulation, strength, toughness, and thermal shock resistance of the obtained ternary aerogel composite material. Summary of the invention

[0009] In view of the shortcomings of the prior art, the present invention provides a high-temperature resistant ternary aerogel composite material and a preparation method thereof. The prepared high-temperature resistant ternary aerogel composite material has excellent thermal insulation, strength, toughness, high-temperature oxidation resistance, thermal shock resistance, hydrophobicity, and also has a relatively low density.

[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0011] A method for preparing a high temperature resistant ternary aerogel composite material, comprising the following steps: preparing a silicon-aluminum sol, preparing a composite silicon nitride whisker, pre-treating, impregnating once, and impregnating twice;

[0012] The method for preparing the silica-alumina sol comprises mixing aluminum isopropoxide, a first portion of anhydrous ethanol, and a first portion of water, stirring the mixture at a stirring speed of 100-200 rpm for 60-70 min at 60-65° C., standing the mixture at room temperature for 3-4 h, taking a supernatant, and adding concentrated hydrochloric acid to the supernatant to adjust the pH value to 3.5-4 to obtain an aluminum sol; mixing ethyl orthosilicate, a second portion of anhydrous ethanol, and a second portion of water, stirring the mixture at a stirring speed of 300-400 rpm for 10-15 min at room temperature, adding concentrated hydrochloric acid to adjust the pH value to 3.5-4, and stirring the mixture at a stirring speed of 300-400 rpm for 17-18 h at 40-45° C. to obtain a silica sol; mixing the aluminum sol and the silica sol, stirring the mixture at a stirring speed of 300-400 rpm for 5-10 min at room temperature, adding glacial acetic acid, and continuing to stir the mixture for 5-10 min to obtain a silica-alumina sol;

[0013] In the preparation of the silica-alumina sol, the mass ratio of aluminum isopropoxide, the first part of anhydrous ethanol, the first part of water, ethyl orthosilicate, the second part of anhydrous ethanol, the second part of water, and glacial acetic acid is 20-22:210-240:12-15:18-20:40-45:2-4:5-5.2;

[0014] The mass concentration of the concentrated hydrochloric acid is 37%;

[0015] The preparation of composite silicon nitride whiskers comprises the following steps: surface modification, primary composite, and secondary composite;

[0016] The surface modification comprises mixing methyltrimethoxysilane and anhydrous ethanol, stirring at a stirring speed of 200-300 rpm for 15-20 minutes at room temperature, adding silicon nitride whiskers, stirring at a stirring speed of 200-300 rpm for 16-17 hours at 60-65° C., filtering, washing the filter residue with anhydrous ethanol for 3-5 times, vacuum drying, mixing with polyvinyl pyrrolidone and water, stirring at a stirring speed of 200-300 rpm for 50-60 minutes at room temperature, filtering, washing the filter residue with water for 3-5 times, and vacuum drying to obtain surface-modified silicon nitride whiskers;

[0017] In the surface modification, the mass ratio of methyltrimethoxysilane, anhydrous ethanol, silicon nitride whisker, polyvinyl pyrrolidone and water is 10-11:6000-6500:90-100:40-42:7600-8000;

[0018] The silicon nitride whisker has a length of 10 μm and a diameter of 2 μm;

[0019] The primary composite comprises mixing aluminum isopropoxide, anhydrous ethanol and water, stirring at 60-65° C. and a stirring speed of 100-200 rpm for 80-90 min, standing at room temperature for 3-4 h, taking a supernatant, adding concentrated hydrochloric acid to the supernatant to adjust the pH to 3.5-4, adding surface-modified silicon nitride whiskers, stirring at a stirring speed of 100-200 rpm for 40-50 min at room temperature, filtering, washing the filter residue with water for 3-5 times, and vacuum drying to obtain a primary composite silicon nitride whisker;

[0020] In the primary compounding, the mass ratio of aluminum isopropoxide, anhydrous ethanol, water, and surface-modified silicon nitride whiskers is 30-31:340-360:18-20:92-95;

[0021] The mass concentration of the concentrated hydrochloric acid is 37%;

[0022] The secondary compounding comprises mixing tetraethyl orthosilicate, anhydrous ethanol and water, stirring at a stirring speed of 300-400 rpm for 10-15 minutes at room temperature, adding concentrated hydrochloric acid to adjust the pH to 3.5-4, stirring at a stirring speed of 300-400 rpm for 19-20 hours at 40-45° C., adding ammonia water to adjust the pH to 8.5-9, continuing to stir for 1-1.5 hours, adding a primary composite silicon nitride whisker, stirring at a stirring speed of 100-200 rpm for 40-50 minutes at room temperature, and obtaining composite silicon nitride whiskers;

[0023] In the secondary composite, the mass ratio of tetraethyl orthosilicate, anhydrous ethanol, water, and primary composite silicon nitride whiskers is 37-40:80-85:5-7:20-25;

[0024] The mass concentration of the concentrated hydrochloric acid is 37%;

[0025] The mass concentration of the ammonia water is 25%;

[0026] The pretreatment comprises mixing methyltrimethoxysilane and anhydrous ethanol, stirring at a stirring speed of 200-300 rpm for 15-20 minutes at room temperature, adding silicon nitride fiber fabric, stirring at a stirring speed of 200-300 rpm for 13-15 hours at 60-65° C., filtering, washing the filter residue with anhydrous ethanol for 3-5 times, vacuum drying, mixing with polyvinyl pyrrolidone and water, stirring at a stirring speed of 200-300 rpm for 80-90 minutes at room temperature, filtering, washing the filter residue with water for 3-5 times, and vacuum drying to obtain the pretreated silicon nitride fiber fabric;

[0027] In the pretreatment, the mass ratio of methyltrimethoxysilane, anhydrous ethanol, silicon nitride fiber fabric, polyvinyl pyrrolidone and water is 14-15:8000-8500:110-120:60-65:8000-8500;

[0028] The thickness of the silicon nitride fiber fabric is 0.3-0.4 mm;

[0029] The primary impregnation comprises adding the pretreated silicon nitride fiber fabric into a mold, adding the mold into a vacuum device, and adding the silicon-aluminum sol after vacuuming to ensure that the pretreated silicon nitride fiber fabric can be completely immersed in the silicon-aluminum sol, standing for 50-60 minutes, and then adding the pretreated silicon nitride fiber fabric into an oven for heat treatment, and then completely immersing the pretreated silicon nitride fiber fabric in anhydrous ethanol for aging to obtain a primary impregnation silicon nitride fiber fabric;

[0030] During the primary impregnation, the vacuum degree of the vacuum equipment is 200-500 Pa;

[0031] The temperature of the oven during the heat treatment is 50-55°C, and the heat treatment time is 50-60min;

[0032] The aging temperature is 50-55° C., the aging time is 70-75 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period;

[0033] The secondary impregnation is to add the once impregnated silicon nitride fiber fabric into a mold, add the mold into a vacuum device, add the composite silicon nitride whisker after vacuuming, ensure that the pretreated silicon nitride fiber fabric can be completely impregnated in the composite silicon nitride whisker, stand for 50-60 minutes, then add it into an oven for heat treatment, then completely immerse it in anhydrous ethanol for aging, then transfer it into a high-pressure reactor to use carbon dioxide for supercritical drying, and then transfer it into a tubular furnace for high-temperature treatment to obtain a high-temperature resistant ternary aerogel composite material;

[0034] During the secondary impregnation, the vacuum degree of the vacuum equipment is 200-500 Pa;

[0035] The temperature of the oven during the heat treatment is controlled to 50-55°C, and the heat treatment time is 50-60 minutes;

[0036] The aging temperature is 50-55° C., the aging time is 70-75 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period;

[0037] In the supercritical drying, the temperature of the autoclave is 55°C, the pressure is 10MPa, and the supercritical drying time is 2.5-3h;

[0038] The high temperature treatment is carried out in an argon atmosphere;

[0039] The high temperature treatment is to increase the temperature to 850-900°C at a heating rate of 3-4°C / min, and stand at 850-900°C for 3-4h.

[0040] A high temperature resistant ternary aerogel composite material prepared by the aforementioned preparation method.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The preparation method of the high temperature resistant ternary aerogel composite material of the present invention, in the preparation of composite silicon nitride whiskers, specifically, firstly using methyltrimethoxysilane to modify the surface of silicon nitride whiskers to obtain hydrophobic silicon nitride whiskers, then using polyvinyl pyrrolidone to modify the surface to improve the hydrophilicity of the silicon nitride whiskers, and then using acidic aluminum sol to adsorb on the surface of silicon nitride whiskers in a first composite, and then using alkaline silica sol to adsorb on the surface of silicon nitride whiskers in a second composite to obtain a mixture of silicon nitride whiskers with alkaline silica sol adsorbed on the surface and alkaline silica sol, i.e., composite silicon nitride whiskers; In the pretreatment, methyltrimethoxysilane is first used to modify the surface of the silicon nitride fiber fabric to obtain a hydrophobic silicon nitride fiber fabric, and then polyvinyl pyrrolidone is used to modify the silicon nitride fiber fabric to improve the hydrophilicity of the silicon nitride fiber fabric to obtain a pretreated silicon nitride fiber fabric; in an impregnation, the pretreated silicon nitride fiber fabric is impregnated with an acidic silicon aluminum sol, and the polyvinyl pyrrolidone on the surface of the pretreated silicon nitride fiber fabric can improve the binding property with the acidic silicon aluminum sol, so that the acidic silicon aluminum sol is coated on the surface of the pretreated silicon nitride fiber fabric to obtain a fabric with good thermal conductivity, low density and strong compression. The invention discloses a single impregnated silicon nitride fiber fabric with high strength, toughness, high temperature oxidation resistance and thermal shock resistance; in the secondary impregnation, the single impregnated silicon nitride fiber fabric is secondary impregnated with composite silicon nitride whiskers, and adsorbed according to the difference in charge between the acidic silicon aluminum sol and the silica sol in the composite silicon nitride whiskers, so that the single impregnated silicon nitride fiber fabric is coated with the composite silicon nitride whiskers and the alkaline silica sol, and finally subjected to high temperature treatment in a tubular furnace, with polyvinyl pyrrolidone as a template agent, thermally decomposed, and the core of the obtained high temperature resistant ternary aerogel composite material is the silicon nitride fiber fabric. The intermediate coating layer is a composite of silica aerogel and alumina aerogel, and the outer coating layer is a composite of silica aerogel, alumina aerogel and silicon nitride whiskers. The presence of silicon nitride whiskers can not only improve the strength and toughness of the high-temperature resistant ternary aerogel composite material, but also reduce the thermal conductivity and density due to the formation of pores after the thermal decomposition of polyvinyl pyrrolidone. In addition, the methyltrimethoxysilane on the surface of the silicon nitride whisker is further cross-linked with the silica aerogel and the alumina aerogel, which can also improve the hydrophobicity of the high-temperature resistant ternary aerogel composite material.

[0043] (2) The method for preparing the high temperature resistant ternary aerogel composite material of the present invention, wherein the prepared high temperature resistant ternary aerogel composite material has excellent thermal insulation and a thermal conductivity coefficient of 0.017-0.020 W / (m·K) at room temperature;

[0044] (3) The method for preparing the high temperature resistant ternary aerogel composite material of the present invention, the prepared high temperature resistant ternary aerogel composite material has excellent strength, and the room temperature compressive strength (3% deformation) is 0.34-0.37MPa;

[0045] (4) The method for preparing the high temperature resistant ternary aerogel composite material of the present invention, wherein the prepared high temperature resistant ternary aerogel composite material has excellent hydrophobicity and a wetting angle of 139.4-141.6° at room temperature;

[0046] (5) The method for preparing the high temperature resistant ternary aerogel composite material of the present invention, wherein the prepared high temperature resistant ternary aerogel composite material has a relatively small density of 0.30-0.31 g / cm 3 ;

[0047] (6) The method for preparing the high temperature resistant ternary aerogel composite material of the present invention, wherein the prepared high temperature resistant ternary aerogel composite material has excellent toughness. The high temperature resistant ternary aerogel composite material prepared by the present invention is cut into square samples with a side length of 20 cm, and the square samples are bent 30 degrees, and no cracks are present during the bending;

[0048] (7) The method for preparing the high temperature resistant ternary aerogel composite material of the present invention, the prepared high temperature resistant ternary aerogel composite material has excellent high temperature oxidation resistance. After the high temperature resistant ternary aerogel composite material prepared by the present invention is placed in air at 1200°C for 1 hour, the room temperature thermal conductivity is 0.018-0.021W / (m·K), and the room temperature compressive strength (3% deformation) is 0.32-0.35MPa;

[0049] (8) The method for preparing a high temperature resistant ternary aerogel composite material of the present invention has excellent thermal shock resistance. The high temperature resistant ternary aerogel composite material prepared by the present invention is heated to 1200°C for 4 hours, kept at 1200°C for 10 minutes, and then cooled to 20°C by cold air as one cycle. After 20 cycles in total, no cracks exist on the surface. DETAILED DESCRIPTION

[0050] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0051] Example 1

[0052] A method for preparing a high temperature resistant ternary aerogel composite material, specifically comprising:

[0053] 1. Preparation of silica-alumina sol: 20 g of aluminum isopropoxide, 210 g of anhydrous ethanol and 12 g of water were mixed, stirred at 60° C. at a stirring speed of 100 rpm for 60 min, allowed to stand at room temperature for 3 h, the supernatant was taken, and concentrated hydrochloric acid with a mass concentration of 37% was added to the supernatant to adjust the pH to 3.5 to obtain aluminum sol; 18 g of ethyl orthosilicate, 40 g of anhydrous ethanol and 2 g of water were mixed, stirred at room temperature at a stirring speed of 300 rpm for 10 min, concentrated hydrochloric acid with a mass concentration of 37% was added to adjust the pH to 3.5, and stirred at 40° C. at a stirring speed of 300 rpm for 17 h to obtain silica sol; all of the above aluminum sol and all of the above silica sol were mixed, stirred at room temperature at a stirring speed of 300 rpm for 5 min, 5 g of glacial acetic acid was added, and stirring was continued for 5 min to obtain silica-alumina sol;

[0054] 2. Preparation of composite silicon nitride whiskers:

[0055] (1) Surface modification: 10 g of methyltrimethoxysilane and 6000 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 200 rpm for 15 min, 90 g of silicon nitride whiskers were added, stirred at 60 ° C at a stirring speed of 200 rpm for 16 h, filtered, the filter residue was washed 3 times with anhydrous ethanol, vacuum dried, mixed with 40 g of polyvinyl pyrrolidone and 7600 g of water, stirred at room temperature at a stirring speed of 200 rpm for 50 min, filtered, the filter residue was washed 3 times with water, and vacuum dried to obtain surface-modified silicon nitride whiskers;

[0056] The silicon nitride whisker has a length of 10 μm and a diameter of 2 μm;

[0057] (2) Primary composite: 30 g of aluminum isopropoxide, 340 g of anhydrous ethanol and 18 g of water were mixed, stirred at 60°C at a stirring speed of 100 rpm for 80 min, allowed to stand at room temperature for 3 h, the supernatant was taken, concentrated hydrochloric acid with a mass concentration of 37% was added to the supernatant to adjust the pH to 3.5, 92 g of surface-modified silicon nitride whiskers was added, stirred at a stirring speed of 100 rpm for 40 min at room temperature, filtered, the filter residue was washed with water for 3 times, and vacuum dried to obtain primary composite silicon nitride whiskers;

[0058] (3) Secondary compounding: 37 g of tetraethyl orthosilicate, 80 g of anhydrous ethanol and 5 g of water were mixed, and the mixture was stirred at 300 rpm for 10 min at room temperature. Concentrated hydrochloric acid with a mass concentration of 37% was added to adjust the pH to 3.5. The mixture was stirred at 300 rpm at 40°C for 19 h. Ammonia water with a mass concentration of 25% was added to adjust the pH to 8.5. The mixture was stirred for 1 h. 20 g of primary composite silicon nitride whiskers was added. The mixture was stirred at 100 rpm for 40 min at room temperature to obtain composite silicon nitride whiskers.

[0059] 3. Pretreatment: 14 g of methyltrimethoxysilane and 8000 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 200 rpm for 15 min, 110 g of silicon nitride fiber fabric was added, stirred at 60 ° C at a stirring speed of 200 rpm for 13 h, filtered, the filter residue was washed 3 times with anhydrous ethanol, vacuum dried, mixed with 60 g of polyvinyl pyrrolidone and 8000 g of water, stirred at room temperature at a stirring speed of 200 rpm for 80 min, filtered, the filter residue was washed 3 times with water, and vacuum dried to obtain pretreated silicon nitride fiber fabric;

[0060] The thickness of the silicon nitride fiber fabric is 0.3 mm;

[0061] 4. One-time impregnation: add the pretreated silicon nitride fiber fabric to the mold, add the mold to the vacuum equipment, evacuate to a vacuum degree of 200Pa, then add the silicon aluminum sol to ensure that the pretreated silicon nitride fiber fabric can be completely immersed in the silicon aluminum sol, let it stand for 50 minutes, then add it to the oven, control the temperature of the oven to 50°C, let it stand for 50 minutes, and then completely immerse it in anhydrous ethanol, let it stand at 50°C for 70 hours, and change the anhydrous ethanol every 10 hours during the standing period to obtain a one-time impregnated silicon nitride fiber fabric;

[0062] 5. Secondary impregnation: Add the once impregnated silicon nitride fiber fabric to the mold, add the mold to the vacuum equipment, evacuate to a vacuum degree of 200Pa, then add the composite silicon nitride whiskers to ensure that the pretreated silicon nitride fiber fabric can be completely impregnated in the composite silicon nitride whiskers, let it stand for 50 minutes, then add it to the oven, control the temperature of the oven to 50°C, let it stand for 50 minutes, and then completely immerse it in anhydrous ethanol, let it stand at 50°C for 70 hours, change the anhydrous ethanol every 10 hours during the standing period, transfer it to a high-pressure reactor and use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 55°C, control the pressure to 10MPa, let it stand for 2.5 hours, transfer it to a tubular furnace, and in an argon atmosphere, heat it to 850°C at a heating rate of 3°C / min, let it stand for 3 hours, and obtain a high-temperature resistant ternary aerogel composite material.

[0063] This embodiment also provides a high temperature resistant ternary aerogel composite material prepared by the aforementioned preparation method.

[0064] Example 2

[0065] A method for preparing a high temperature resistant ternary aerogel composite material, specifically comprising:

[0066] 1. Preparation of silica-alumina sol: 21 g of aluminum isopropoxide, 220 g of anhydrous ethanol and 14 g of water were mixed, stirred at 62° C. at a stirring speed of 150 rpm for 65 min, allowed to stand at room temperature for 3.5 h, the supernatant was taken, and concentrated hydrochloric acid with a mass concentration of 37% was added to the supernatant to adjust the pH to 3.5 to obtain aluminum sol; 19 g of ethyl orthosilicate, 42 g of anhydrous ethanol and 3 g of water were mixed, stirred at room temperature at a stirring speed of 350 rpm for 12 min, concentrated hydrochloric acid with a mass concentration of 37% was added to adjust the pH to 3.5, and stirred at 42° C. at a stirring speed of 350 rpm for 17.5 h to obtain silica sol; all of the above aluminum sol and all of the above silica sol were mixed, stirred at room temperature at a stirring speed of 350 rpm for 8 min, 5.1 g of glacial acetic acid was added, and stirring was continued for 8 min to obtain silica-alumina sol;

[0067] 2. Preparation of composite silicon nitride whiskers:

[0068] (1) Surface modification: 10.5 g of methyltrimethoxysilane and 6200 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 250 rpm for 18 min, 95 g of silicon nitride whiskers were added, stirred at 62 ° C at a stirring speed of 250 rpm for 16.5 h, filtered, the filter residue was washed with anhydrous ethanol for 4 times, vacuum dried, mixed with 41 g of polyvinyl pyrrolidone and 7800 g of water, stirred at room temperature at a stirring speed of 250 rpm for 55 min, filtered, the filter residue was washed with water for 4 times, and vacuum dried to obtain surface-modified silicon nitride whiskers;

[0069] The silicon nitride whisker has a length of 10 μm and a diameter of 2 μm;

[0070] (2) Primary composite: 30.5 g of aluminum isopropoxide, 350 g of anhydrous ethanol and 19 g of water were mixed, stirred at 62 °C at a stirring speed of 150 rpm for 85 min, allowed to stand at room temperature for 3.5 h, the supernatant was taken, 37% concentrated hydrochloric acid was added to the supernatant to adjust the pH to 3.5, 94 g of surface-modified silicon nitride whiskers were added, stirred at room temperature at a stirring speed of 150 rpm for 45 min, filtered, the filter residue was washed with water for 4 times, and vacuum dried to obtain primary composite silicon nitride whiskers;

[0071] (3) Secondary compounding: 38 g of tetraethyl orthosilicate, 82 g of anhydrous ethanol and 6 g of water were mixed, and the mixture was stirred at 350 rpm for 12 min at room temperature. Concentrated hydrochloric acid with a mass concentration of 37% was added to adjust the pH to 3.8. The mixture was stirred at 350 rpm for 19.5 h at 42 °C. Ammonia water with a mass concentration of 25% was added to adjust the pH to 8.5. The mixture was stirred for 1 h. 22 g of primary composite silicon nitride whiskers was added. The mixture was stirred at 150 rpm for 45 min at room temperature to obtain composite silicon nitride whiskers.

[0072] 3. Pretreatment: 14.5 g of methyltrimethoxysilane and 8200 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 250 rpm for 18 min, 115 g of silicon nitride fiber fabric was added, stirred at 62 ° C at a stirring speed of 250 rpm for 14 h, filtered, the filter residue was washed 4 times with anhydrous ethanol, vacuum dried, mixed with 62 g of polyvinyl pyrrolidone and 8200 g of water, stirred at room temperature at a stirring speed of 250 rpm for 85 min, filtered, the filter residue was washed 4 times with water, and vacuum dried to obtain pretreated silicon nitride fiber fabric;

[0073] The thickness of the silicon nitride fiber fabric is 0.3 mm;

[0074] 4. One-time impregnation: add the pretreated silicon nitride fiber fabric to the mold, add the mold to the vacuum equipment, evacuate to a vacuum degree of 300Pa, then add the silicon aluminum sol to ensure that the pretreated silicon nitride fiber fabric can be completely immersed in the silicon aluminum sol, let it stand for 55 minutes, then add it to the oven, control the temperature of the oven to 52°C, let it stand for 55 minutes, and then completely immerse it in anhydrous ethanol, let it stand at 52°C for 72 hours, and change the anhydrous ethanol every 11 hours during the standing period to obtain a one-time impregnated silicon nitride fiber fabric;

[0075] 5. Secondary impregnation: Add the once-impregnated silicon nitride fiber fabric to the mold, add the mold to the vacuum equipment, evacuate to a vacuum degree of 300Pa, then add the composite silicon nitride whiskers to ensure that the pretreated silicon nitride fiber fabric can be completely impregnated in the composite silicon nitride whiskers, let it stand for 55 minutes, then add it to the oven, control the temperature of the oven to 52°C, let it stand for 55 minutes, and then completely immerse it in anhydrous ethanol, let it stand at 52°C for 72 hours, change the anhydrous ethanol every 11 hours during the standing period, transfer it to a high-pressure reactor and use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 55°C, control the pressure to 10MPa, let it stand for 2.5 hours, transfer it to a tubular furnace, and in an argon atmosphere, heat it to 880°C at a heating rate of 3°C / min, let it stand for 3.5 hours, and obtain a high-temperature resistant ternary aerogel composite material.

[0076] This embodiment also provides a high temperature resistant ternary aerogel composite material prepared by the aforementioned preparation method.

[0077] Example 3

[0078] A method for preparing a high temperature resistant ternary aerogel composite material, specifically comprising:

[0079] 1. Preparation of silica-alumina sol: 22g of aluminum isopropoxide, 240g of anhydrous ethanol and 15g of water were mixed, stirred at 65°C at a stirring speed of 200rpm for 70min, allowed to stand at room temperature for 4h, the supernatant was taken, and concentrated hydrochloric acid with a mass concentration of 37% was added to the supernatant to adjust the pH to 4 to obtain aluminum sol; 20g of ethyl orthosilicate, 45g of anhydrous ethanol and 4g of water were mixed, stirred at room temperature at a stirring speed of 400rpm for 15min, concentrated hydrochloric acid with a mass concentration of 37% was added to adjust the pH to 4, and stirred at 45°C at a stirring speed of 400rpm for 18h to obtain silica sol; all of the above aluminum sol and all of the above silica sol were mixed, stirred at room temperature at a stirring speed of 400rpm for 10min, 5.2g of glacial acetic acid was added, and stirring was continued for 10min to obtain silica-alumina sol;

[0080] 2. Preparation of composite silicon nitride whiskers:

[0081] (1) Surface modification: 11 g of methyltrimethoxysilane and 6500 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 300 rpm for 20 min, 100 g of silicon nitride whiskers were added, stirred at 65 ° C at a stirring speed of 300 rpm for 17 h, filtered, the filter residue was washed with anhydrous ethanol for 5 times, vacuum dried, mixed with 42 g of polyvinyl pyrrolidone and 8000 g of water, stirred at room temperature at a stirring speed of 300 rpm for 60 min, filtered, the filter residue was washed with water for 5 times, and vacuum dried to obtain surface-modified silicon nitride whiskers;

[0082] The silicon nitride whisker has a length of 10 μm and a diameter of 2 μm;

[0083] (2) Primary composite: 31 g of aluminum isopropoxide, 360 g of anhydrous ethanol and 20 g of water were mixed, stirred at 65°C at a stirring speed of 200 rpm for 90 min, allowed to stand at room temperature for 4 h, the supernatant was taken, concentrated hydrochloric acid with a mass concentration of 37% was added to the supernatant to adjust the pH to 4, 95 g of surface-modified silicon nitride whiskers was added, stirred at a stirring speed of 200 rpm for 50 min at room temperature, filtered, the filter residue was washed with water for 5 times, and vacuum dried to obtain primary composite silicon nitride whiskers;

[0084] (3) Secondary compounding: 40 g of tetraethyl orthosilicate, 85 g of anhydrous ethanol and 7 g of water were mixed, and stirred at 400 rpm for 15 min at room temperature. Concentrated hydrochloric acid with a mass concentration of 37% was added to adjust the pH to 4. The mixture was stirred at 400 rpm at 45°C for 20 h. Ammonia water with a mass concentration of 25% was added to adjust the pH to 9. The mixture was stirred for 1.5 h. 25 g of primary composite silicon nitride whiskers was added. The mixture was stirred at 200 rpm for 50 min at room temperature to obtain composite silicon nitride whiskers.

[0085] 3. Pretreatment: 15 g of methyltrimethoxysilane and 8500 g of anhydrous ethanol were mixed, stirred at room temperature at a stirring speed of 300 rpm for 20 min, 120 g of silicon nitride fiber fabric was added, stirred at 65 ° C at a stirring speed of 300 rpm for 15 h, filtered, the filter residue was washed 5 times with anhydrous ethanol, vacuum dried, mixed with 65 g of polyvinyl pyrrolidone and 8500 g of water, stirred at room temperature at a stirring speed of 300 rpm for 90 min, filtered, the filter residue was washed 5 times with water, and vacuum dried to obtain pretreated silicon nitride fiber fabric;

[0086] The thickness of the silicon nitride fiber fabric is 0.4 mm;

[0087] 4. One-time impregnation: add the pretreated silicon nitride fiber fabric to the mold, add the mold to the vacuum equipment, evacuate to a vacuum degree of 500Pa, then add the silicon aluminum sol to ensure that the pretreated silicon nitride fiber fabric can be completely immersed in the silicon aluminum sol, let it stand for 60 minutes, then add it to the oven, control the temperature of the oven to 55°C, let it stand for 60 minutes, and then completely immerse it in anhydrous ethanol, let it stand at 55°C for 75 hours, and change the anhydrous ethanol every 12 hours during the standing period to obtain a one-time impregnated silicon nitride fiber fabric;

[0088] 5. Secondary impregnation: Add the once impregnated silicon nitride fiber fabric to the mold, add the mold to the vacuum equipment, evacuate to a vacuum degree of 500Pa, then add the composite silicon nitride whiskers to ensure that the pretreated silicon nitride fiber fabric can be completely impregnated in the composite silicon nitride whiskers, let it stand for 60 minutes, then add it to the oven, control the temperature of the oven to 55°C, let it stand for 60 minutes, and then completely immerse it in anhydrous ethanol, let it stand at 55°C for 75 hours, change the anhydrous ethanol every 12 hours during the standing period, transfer it to a high-pressure reactor and use carbon dioxide for supercritical drying, control the temperature of the high-pressure reactor to 55°C, control the pressure to 10MPa, let it stand for 3 hours, transfer it to a tubular furnace, and in an argon atmosphere, heat it to 900°C at a heating rate of 4°C / min, let it stand for 4 hours, and obtain a high-temperature resistant ternary aerogel composite material.

[0089] This embodiment also provides a high temperature resistant ternary aerogel composite material prepared by the aforementioned preparation method.

[0090] Comparative Example 1

[0091] On the basis of the preparation method of Example 2, the second step of preparing composite silicon nitride whiskers and the fifth step of secondary impregnation are omitted, that is, the single-impregnation silicon nitride fiber fabric prepared in the fourth step of primary impregnation is directly used as a high-temperature resistant ternary aerogel composite material.

[0092] The rest of the technical solutions are the same as those in Example 2.

[0093] Comparative Example 2

[0094] On the basis of the preparation method of Example 2, the pretreatment step in step 3 is omitted, and in the first impregnation step in step 4, a silicon nitride fiber fabric with a thickness of 0.3 mm is used instead of the pretreated silicon nitride fiber fabric.

[0095] The rest of the technical solutions are the same as those in Example 2.

[0096] Performance Test 1

[0097] The room temperature thermal conductivity, room temperature compressive strength, room temperature wetting angle, and density of the high temperature resistant ternary aerogel composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the test results are as follows:

[0098]

[0099] Performance Test 2

[0100] The high temperature resistant ternary aerogel composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were cut into square samples with a side length of 20 cm, and the square samples were bent 30 degrees to observe whether there were cracks at the bend. The observation results were as follows:

[0101]

[0102] Performance Test 3

[0103] The high temperature resistant ternary aerogel composite materials prepared in Example 1-3 and Comparative Example 1-2 were placed in air at 1200°C for 1 hour, and then the room temperature thermal conductivity and room temperature compressive strength were tested. The test results are as follows:

[0104]

[0105] Performance Test 4

[0106] The high temperature resistant ternary aerogel composite materials prepared in Examples 1-3 and Comparative Examples 1-2 were heated to 1200°C for 4 hours, kept at 1200°C for 10 minutes, and then cooled to 20°C by cold air. This was regarded as one cycle. A total of 20 cycles were performed to observe whether there were cracks on the surface of the high temperature resistant ternary aerogel composite materials. The observation results were as follows:

[0107]

[0108] It can be seen from the above results that the high temperature resistant ternary aerogel composite materials prepared in Examples 1-3 have excellent room temperature compressive strength, room temperature wetting angle, toughness, high temperature oxidation resistance, thermal shock resistance, and low room temperature thermal conductivity and density; however, compared with the high temperature resistant ternary aerogel composite material prepared in Example 2, the high temperature resistant ternary aerogel composite material prepared in Comparative Example 1 has the problems of large room temperature thermal conductivity and density, small room temperature compressive strength and room temperature wetting angle, and poor toughness, high temperature oxidation resistance and thermal shock resistance; compared with the high temperature resistant ternary aerogel composite material prepared in Example 2, the high temperature resistant ternary aerogel composite material prepared in Comparative Example 2 has the problems of large room temperature thermal conductivity and density, small room temperature compressive strength, and poor toughness, high temperature oxidation resistance and thermal shock resistance.

[0109] Unless otherwise specified, all percentages used in the present invention are by mass.

[0110] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature resistant ternary aerogel composite material, characterized in that: The method comprises the following steps: preparing silicon-aluminum sol, preparing composite silicon nitride whiskers, pre-treating, first dipping, and second dipping; In the preparation of the silica-alumina sol, aluminum isopropoxide, a first portion of anhydrous ethanol, and a first portion of water are mixed, stirred at 60-65° C., allowed to stand at room temperature, a supernatant is taken, and the pH is adjusted to 3.5-4 to obtain an aluminum sol; ethyl orthosilicate, a second portion of anhydrous ethanol, and a second portion of water are mixed, stirred at room temperature, the pH is adjusted to 3.5-4, and stirred at 40-45° C. to obtain a silica sol; the aluminum sol and the silica sol are mixed, stirred at room temperature, glacial acetic acid is added, and stirring is continued to obtain a silica-alumina sol; The preparation of composite silicon nitride whiskers comprises the following steps: surface modification, primary composite, and secondary composite; The surface modification comprises mixing methyltrimethoxysilane and anhydrous ethanol, stirring at room temperature, adding silicon nitride whiskers, stirring at 60-65° C., filtering, washing the filter residue and vacuum drying, mixing with polyvinyl pyrrolidone and water, stirring at room temperature, filtering, washing the filter residue and vacuum drying to obtain surface-modified silicon nitride whiskers; The primary composite comprises mixing aluminum isopropoxide, anhydrous ethanol and water, stirring at 60-65° C., standing at room temperature, taking the supernatant, adjusting the pH to 3.5-4, adding the surface-modified silicon nitride whisker, stirring at room temperature, filtering, washing the filter residue and vacuum drying to obtain the primary composite silicon nitride whisker; The secondary compounding comprises mixing tetraethyl orthosilicate, anhydrous ethanol and water, stirring at room temperature, adjusting the pH to 3.5-4, stirring at 40-45° C., adjusting the pH to 8.5-9, continuing to stir, adding primary composite silicon nitride whiskers, stirring at room temperature, and obtaining composite silicon nitride whiskers; The pretreatment comprises mixing methyltrimethoxysilane and anhydrous ethanol, stirring at room temperature, adding silicon nitride fiber fabric, stirring at 60-65° C., filtering, washing the filter residue and vacuum drying, mixing with polyvinyl pyrrolidone and water, stirring at room temperature, filtering, washing the filter residue and vacuum drying to obtain pretreated silicon nitride fiber fabric; The primary impregnation comprises adding the pretreated silicon nitride fiber fabric into a mold, adding the mold into a vacuum device, and adding the silicon-aluminum sol after vacuuming to ensure that the pretreated silicon nitride fiber fabric can be completely immersed in the silicon-aluminum sol, standing, and then adding the pretreated silicon nitride fiber fabric into an oven for heat treatment, and then completely immersing the pretreated silicon nitride fiber fabric in anhydrous ethanol for aging to obtain a primary impregnation silicon nitride fiber fabric; The secondary impregnation comprises adding the once impregnated silicon nitride fiber fabric into a mold, adding the mold into a vacuum device, and adding composite silicon nitride whiskers after vacuuming to ensure that the pretreated silicon nitride fiber fabric can be completely impregnated in the composite silicon nitride whiskers, standing, and then adding the fabric into an oven for heat treatment, and then completely immersing the fabric in anhydrous ethanol for aging, and then transferring the fabric into a high-pressure reactor to use carbon dioxide for supercritical drying, and then transferring the fabric into a tubular furnace for high-temperature treatment to obtain a high-temperature resistant ternary aerogel composite material.

2. The method for preparing the high temperature resistant ternary aerogel composite material according to claim 1, characterized in that: In the preparation of the silica-alumina sol, the mass ratio of aluminum isopropoxide, the first part of anhydrous ethanol, the first part of water, ethyl orthosilicate, the second part of anhydrous ethanol, the second part of water, and glacial acetic acid is 20-22:210-240:12-15:18-20:40-45:2-4:5-5.

2.

3. The method for preparing the high temperature resistant ternary aerogel composite material according to claim 1, characterized in that: In the surface modification, the mass ratio of methyltrimethoxysilane, anhydrous ethanol, silicon nitride whisker, polyvinyl pyrrolidone and water is 10-11:6000-6500:90-100:40-42:7600-8000; The silicon nitride whisker has a length of 10 μm and a diameter of 2 μm; In the primary compounding, the mass ratio of aluminum isopropoxide, anhydrous ethanol, water, and surface-modified silicon nitride whiskers is 30-31:340-360:18-20:92-95; In the secondary composite, the mass ratio of tetraethyl orthosilicate, anhydrous ethanol, water, and primary composite silicon nitride whiskers is 37-40:80-85:5-7:20-25.

4. The method for preparing the high temperature resistant ternary aerogel composite material according to claim 1, characterized in that: In the pretreatment, the mass ratio of methyltrimethoxysilane, anhydrous ethanol, silicon nitride fiber fabric, polyvinyl pyrrolidone and water is 14-15:8000-8500:110-120:60-65:8000-8500; The thickness of the silicon nitride fiber fabric is 0.3-0.4 mm.

5. The method for preparing the high temperature resistant ternary aerogel composite material according to claim 1, characterized in that: During the primary impregnation, the vacuum degree of the vacuum equipment is 200-500 Pa; The temperature of the oven during the heat treatment is 50-55°C, and the heat treatment time is 50-60min; The aging temperature is 50-55° C., the aging time is 70-75 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period.

6. The method for preparing the high temperature resistant ternary aerogel composite material according to claim 1, characterized in that: During the secondary impregnation, the vacuum degree of the vacuum equipment is 200-500 Pa; The temperature of the oven during the heat treatment is controlled to 50-55°C, and the heat treatment time is 50-60 minutes; The aging temperature is 50-55° C., the aging time is 70-75 hours, and the anhydrous ethanol is replaced every 10-12 hours during the aging period; In the supercritical drying, the temperature of the autoclave is 55°C, the pressure is 10MPa, and the supercritical drying time is 2.5-3h; The high temperature treatment is carried out in an argon atmosphere; The high temperature treatment is to increase the temperature to 850-900°C at a heating rate of 3-4°C / min, and stand at 850-900°C for 3-4h.

7. A high temperature resistant ternary aerogel composite material prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing heat-resisting alumina-silox aerogel thermal-protective composite material

    CN101792299A